INTERVENTION MANAGEMENT OF 5 PILLARS OF DIABETES MELLITUS CONTROL IN DIABETES MELLITUS DISEASE - Rosandra Firdi Silviana; Sutiyono Sutiyono (The Shine Cahaya Dunia D-III Keperawatan, 2023)
Background: Diabetes mellitus is a non-communicable disease that causes many deaths throughout the world. Diabetes Mellitus is a disease characterized by an increase in blood glucose levels above the normal range, namely 90-140 mg/dl. Management of Diabetes Mellitus with 5 pillars includes education, physical exercise, dietary intervention, medication, and blood sugar checks. Implementation of the 5 pillars in treating Diabetes Mellitus is necessary to improve quality of life. Objective: To provide family nursing care to Mr. R with a Focus on Interventions for Managing the 5 Pillars of Diabetes Mellitus Control in Diabetes Mellitus in Menduran Village, Brati District, Grobogan Regency.Methodology: The type of research used by researchers in this paper is qualitative with a descriptive approach. The design used in the research is a case study. The research subjects are especially Mr. R who suffers from Diabetes Mellitus.Results: Researchers identified that after managing the 5 pillars of Diabetes Mellitus control during 3 visits, Mr. R especially Mr. R experienced a decrease in blood glucose levels from 210 mg/dl to 162 mg/dl at the final examination.Conclusion: There is an influence on the effectiveness of managing the 5 pillars of Diabetes Mellitus control to help reduce blood glucose levels, Mr. R with Hyperglycemia problems.